The generalized riccati equation together with the (G' / G) -Expansion method for the (3+1)-dimensional modified KDV-zakharov-kuznetsov equation - Naher, Hasibun; Abdullah, Farah Aini; Rashid, Abdur (© 2014 Politechnica University of Bucharest, 2016)
This article was published in the UPB Scientific Bulletin, Series A: Applied Mathematics and Physics [© 2014 Politechnica University of Bucharest ] The Journal's website is at: http://www.scientificbulletin.upb.ro/rev_docs_arhiva/full78d_557338.pdf